ANALISIS CFD DISTRIBUSI TEMPERATUR DAN KELEMBABAN RELATIF PADA PROSES DEHUMIDIFIKASI SAMPLE HOUSE DENGAN KONSENTRASI LIQUID DESSICANT 30% - Bondantio Putro; Eflita Yohana; Bambang Yunianto (JURNAL TEKNIK MESIN, 2015)
There are various methods used to control the humidity in the room, one of them with a dehumidification system. By utilizing a liquid desiccant such as CaCl 2, relative humidity values can be suppressed in accordance with the specified variable. To determine the distribution of temperature and relative humidity in the room needed numerical simulations using Computational Fluid Dynamics (CFD). The model used in the experiment room (L = 1500 mm, W = 1000 mm, H = 1500 mm) is used to determine the ability of liquid desiccant in reducing humidity. Tests carried out in the morning at 08.00 with liquid desiccant concentration of 30%, as well as the dimensions of 0.2 mm nozzel, and discharge air to enter the room guarded by 2.35 m3 / min. At the inlet and outlet sides of the room fitted DHT sensor 11, which serves to record the changes in humidity and temperature during the test. In normal conditions without turning tool dehumidifier, sensors record the average temperature in the room at 28°C and 68% RH. The simulation was performed using CFD software Solidworks Flow Simulation 2014. Simulation results show that the distribution of temperature and relative humidity in the room with liquid desiccant concentration 30% runs into a  poor relative humidity, the RH average of 67.5% followed by the increase in air temperature 28.5 ° C and it  also contains not maximum temperature distribution and RH.